(untitled) (Acta Entomologica Serbica, 2022)
This paper lists the current fauna of Aphrophoridae family in Morocco. Distribution data of their occurrence in the country are provided. Nine species of aphrophorid spittlebugs found in Morocco are listed, five of them identified and described for the first time in the country and four other species reported in the literature. An identification key of aphrophorid genera and species is given. The Mediterranean spittlebug Philaenus tesselatus Melichar, 1899 (Moroccan specimen) is described and differentiated from the European meadow spittlebug Philaenus spumarius Linnaeus, 1758 (Italian specimen). The newly reported Philaenus sp. specimen found in Morocco is described.